Additive Manufacturing in Biomedical Applications 2022
DOI: 10.31399/asm.hb.v23a.a0006853
|View full text |Cite
|
Sign up to set email alerts
|

Zirconia for Dental Implants

Abstract: One of the most frequently cited advantages of ceramics in dentistry relates to aesthetics, and the same applies for dental implants. Zirconia has emerged as the material of choice for nonmetal implants. This article introduces the reader to zirconia as an implant material, its properties, manufacturing processes, and the particular surface modifications and treatments that have rendered its surfaces biologically compatible with peri-implant soft and hard tissues.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 67 publications
0
11
0
Order By: Relevance
“…Its use in the treatment of partially or completely edentulous patients has become an integral part of dental treatment nevertheless patients with mental illnesses face many difficulties in relation to implant treatment. 13,14 Treatment of such patients is usually possible only under general anesthesia in highly specialized centers with appropriate equipment and experienced medical staff. The issue of high costs of implant treatment, limited access to detailed information on the advancement of the disease, and little data on the effectiveness of treatment in patients with mental illnesses often lead to the resignation of this method in favor of removable acrylic dentures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use in the treatment of partially or completely edentulous patients has become an integral part of dental treatment nevertheless patients with mental illnesses face many difficulties in relation to implant treatment. 13,14 Treatment of such patients is usually possible only under general anesthesia in highly specialized centers with appropriate equipment and experienced medical staff. The issue of high costs of implant treatment, limited access to detailed information on the advancement of the disease, and little data on the effectiveness of treatment in patients with mental illnesses often lead to the resignation of this method in favor of removable acrylic dentures.…”
Section: Discussionmentioning
confidence: 99%
“…A dental implant is one of the possibilities to replace missing teeth. Its use in the treatment of partially or completely edentulous patients has become an integral part of dental treatment nevertheless patients with mental illnesses face many difficulties in relation to implant treatment 13,14 . Treatment of such patients is usually possible only under general anesthesia in highly specialized centers with appropriate equipment and experienced medical staff.…”
Section: Discussionmentioning
confidence: 99%
“…Dental implant is one of the most common dental treatments to replace missing teeth. The primarily function of a dental implant is restoring the patient to a normal profile regardless of the status of the stomatognathic system [130,131]. Similar to the orthopedic implants, conventional dental implant relies on titanium as implant materials to fulfill several requirements: (1) good fatigue strength and wear resistance to withstand cyclic occlusal load (axial bite force: 500 N-800 N) [132][133][134], (2) good corrosion resistance to withstand different types of corrosions that take place in the oral cavity (galvanic, pitting, stress, and microbial corrosion) [128,135], and (3) bioinert to body environment and good biocompatibility [136].…”
Section: Polymer-metal Composite Materials For Dental Implantmentioning
confidence: 99%
“…The studies of Gupta et al showed a high success rate, around 97% after a follow-up of 10 years. 1 Gay and colleagues through a retrospective study evidenced the survival rate of implants placed in the native bone and regenerated bone after 5 and 10 years were 92 and 87% for implants placed in the native bone, and 90 and 79% for implants placed in the grafted bone. 2 After tooth extraction, on the edentulous site occur morphological and dimensional changes of the alveolar ridge due to qualitative and quantitative modification.…”
Section: Introductionmentioning
confidence: 99%